DAMPAK SEKTOR PARIWISATA DAN LINGKUNGAN HIDUP TERHADAP PEMBANGUNAN BANDARA INTERNASIONAL YOGYAKARTA (YIA) - Oktarizka Reviandani; Indira Arundinasari (GEMA PUBLICA, 2023)
The crisis in the environmental and development aspects always creates conflict for government, private, and community actors. The focus of this research is to analyze YIA's development policies. This study uses qualitative research methods with an interpretive paradigm. The results of this study indicate that the phenomenon of policy debate in the struggle for interests by the rival coalition over the rejection of YIA development is due to its influence on the tourism sector and in particular the environmental impact. The formation of a counter-coalition consisting of the main coalition and the supporting coalition has a strong influence in attracting a broad base of supporting movements. The groups in the counter-united coalition are driven by a common belief system, ranging from the most general to specific beliefs, namely the community's close attachment to land, a community-friendly development perspective, and the impact of YIA. When the counter-coalition was built, various counter-coalition groups were motivated to translate this belief into policy actions ranging from formal legal channels, public communication, scientific information, and mass movements. Various resources and strategies support each other, especially in the two aspects that are most powerful in influencing policy, namely information sources and financial sources.